2014
DOI: 10.21608/eajbsc.2014.16047
|View full text |Cite
|
Sign up to set email alerts
|

The curative effect of Bee Venom and Propolis on oxidative stress induced by γ-irradiation on blood and tissues of rats

Abstract: and is devoted to publication of original papers that elucidate important biological, chemical, or physical mechanisms logical significance. of broad physio www.eajbs.eg.net Provided for non-commercial research and education use. Not for reproduction, distribution or commercial use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…However, the reduction of lipid peroxidation-mediated oxidative stress may be an effective strategy for the prevention and treatment of hepatorenal injuries. Inconsistent with the report of both Abdel-rahman and AbdelMoneim [42], and Elshater et al [43], the present study showed that treatment of GM pretreated rats with NnvE significantly decreased MDA levels which may be due to its antioxidant mechanism. Several reports stated that bee venom therapy is a potent antioxidant that led to a decrease in the levels of reactive oxygen species (ROS) [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…However, the reduction of lipid peroxidation-mediated oxidative stress may be an effective strategy for the prevention and treatment of hepatorenal injuries. Inconsistent with the report of both Abdel-rahman and AbdelMoneim [42], and Elshater et al [43], the present study showed that treatment of GM pretreated rats with NnvE significantly decreased MDA levels which may be due to its antioxidant mechanism. Several reports stated that bee venom therapy is a potent antioxidant that led to a decrease in the levels of reactive oxygen species (ROS) [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…Bee venom and its bradykinin-potentiating factor protection against hepatoand nephrotoxicity were reported (Bekheeta, Awadallaa, Salmanb, & Hassan, 2013;Darwish et al, 2013). Moreover, bee venom has a protective effect against impairment in liver and kidney tissues that is induced by gamma radiation where bee venom had significantly decreased the elevation of serum ALT, AST, and ALP (Elshater et al, 2014). The hepatoprotective effect of bee venom was attributed to inhibiting the secretion of pro-inflammatory cytokines and decreasing the elevated serum aminotransferase enzymes in different models of induced hepatic injury and nephrotoxicity (Hegazi, 2012;Hyunseong et al, 2013;Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to treat a variety of diseases and complications such as arthritis, rheumatism, back pain, cancerous tumors, and skin disease (Tu, Wu, Hsieh, Chen, & Hsu, 2008;Jang et al, 2009;Lee et al, 2009). Also, bee venom has a curative effect on oxidative stress induced by γ-irradiation (Elshater, Mohi Eldin, Salman, & Kasem, 2014) and protective effect against acute pancreatitis (Seo et al, 2008). In addition, several biological properties were reported such as neuroprotection (Khalil, Assaf, ElShebiney, & Salem, 2015;Yoon & Lee, 2013), beneficial effects in the treatment of Parkinson disease (Alvarez- Fischer et al, 2013), decrease in the complications of diabetes and multiple sclerosis (Chen & Lariviere, 2010;Javad, Adeleh, & Ali, 2014;Orśolić, 2012;Son et al, 2007), hepatoprotective characteristics (Darwish, El-Bakly, Arafa, & El-Demerdash, 2013), and anticancer and radioprotective characteristics (Gajski & Garaj-Vrhovac, 2009;Orśolić, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters included body mass, lean body mass, fat tissue mass, serum lipids, blood sugar, uric acid, arterial pressure, and pulse rate before and after functional loading tests 32 . Furthermore, a combination of propolis and bee venom showed a marked curative effect on OS produced by gamma radiation in rats 33 . Additionally, a combination treatment consisting of aqueous extract of propolis and bee venom induced synergistic antiproliferative effects in breast cancer cells 34 .…”
Section: Introductionmentioning
confidence: 94%